Decoupling Growth from Growth-dependent Planning Paradigms: Contesting Prevailing Urban Renewal Futures in Sydney, Australia. Issue 4 (1st October 2020) - Pinnegar, Simon; Randolph, Bill; Troy, Laurence
ABSTRACT: With the population of Sydney expected to reach 7 million+ in the next 20 years, current strategic planning policy is firmly growth oriented in its aims, and growth dependent in its settings, with a key focus on promoting higher density redevelopment around rail stations through value uplift. Using the Sydenham-to-Bankstown Corridor as our case study, this paper engages with the contradictions underpinning current templates for market-driven urban renewal. Questioning models privileging a financialised, hypertrophic reconfiguration of existing neighbourhoods, we examine the business of densification and its spatial manifestation(s) to explore potential frameworks for greater inclusivity in both the process, and outcomes, of suburban growth. 摘要： 随着悉尼人口在未来20年内预计将达到700万以上，目前的战略规划政策的目标是坚定地以增长为导向，并在其环境中依赖增长，重点是通过价值提升促进火车站周围更高密度的再开发. 本文以西德纳姆-班克斯敦走廊为例，探讨了当前市场驱动的城市更新模式所存在的矛盾. 在质疑现有街区金融化、过度重组的模式时，我们研究了密集化的业务及其空间表现形式，以探索郊区发展过程和结果中更大包容性的潜在框架